COMPARATIVE ACHIEVEMENTS OF SEVENTH-DAY ADVENTIST LEADERSHIP IN INDONESIA PRE AND POST 1970 - Rexon Nainggolan (Jurnal Theologia Forum STFT Surya Nusantara, 2019)
The year 1970 is an important milestone in Seventh-day Adventist organization in Indonesia. First, as the Union of Indonesia was organized in 1929, 1970 is relatively the middle of the Indonesia movement up to now. Second, started in 1970 the leadership in the two Indonesia unions were transferred from non-Indonesian leaders to the native Indonesian. In that relation, this study compares the achievements of the Seventh-day Adventist church leadership in Indonesia pre and post 1970, the year when the leaderships were transferred from non-Indonesian to the native Indonesian, from the view of membership, numbers of churches, as well as the institutional and landmarks establishments.The finding indicates that the achievements of Seventh-day Adventist church in Indonesia under leadership of native Indonesia post 1970 is significantly decrease when compared to the non-Indonesian leadership in previous period from the view of membership growth(83.55%) and number of churches (102.94%). This conclusion is indicated by average annual membership growth which decreases from 7.81% in Period 1 of to 3.56% in Period 2 and the average annual number of churches growth which decreases from 5.30% in Period 1 of to 2.69%. The statistical data also reported that most of current major institutions and landmarks were established during the leadership of non-Indonesian. Nevertheles, the leadership in Period 2 had maintained the institutions and developed them into more sophisticated institutions. Keywords: Seventh-day Adventist Church , leadership, membership growth, number of churches